Factors Influencing Technical Efficiency of the Rice (Oryza sativa) Farming - Jamaludin Adi Prabowo; Fahriyah Fahriyah; Syafrial Syafrial (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Increasing production and productivity, primarily done in the rice production centers, is the main focus to reduce the rate of rice imports in Indonesia. Measuring technical efficiency and analyzing factors influencing of rice farming is important in order to achieve maximum production and to obtain maximum profits. This study aims to determine the level of technical efficiency of rice farming analyze factors affecting rice farming. The research location was chosen purposively in Kedungadem, Kalitidu, and Kapas Districts with a sample of 150 rice farmers using simple random sampling. The analytical methods used Data Envelopment Analysis (DEA) with the Variable Return to Scale (VRS) model to measure technical efficiency, while tobit regression analysis to identify factors affecting technical efficiency, and farm income analysis. The research results indicate that the factors significantly affecting technical efficiency are land size, level of formal education, farming experience, and land ownership status. The technical efficiency level of rice farming in the study areas, assessed using the DEA approach under the VRS assumption, was classified to be moderate efficient. However, rice farming in the study sites can be considered as profitable. Keywords: Education, Land ownership, Land size, Variable Return to Scale (VRS).